Positioning tezepelumab for patients with severe asthma: from evidence to unmet needs - Carlo Lombardi; Marcello Cottini; Annamaria Bosi; Francesco Menzella (Journal of International Medical Research)
Several endotypes of severe asthma with predominantly type 2 inflammation can be distinguished by the immune pathways driving the inflammatory processes. However, in the absence of type 2 inflammation, asthma is less clearly defined and is generally associated with poor responses to conventional anti-asthmatic therapies. Studies have shown that disruption of the epithelial barrier triggers inflammatory responses and increases epithelial permeability. A key aspect of this process is that epithelial cells release alarmin cytokines, including interleukin (IL)-25, IL-33, and thymic stromal lymphopoietin (TSLP), in response to allergens and infections. Among these cytokines, TSLP has been identified as a potential therapeutic target for severe asthma, leading to the development of a new biologic, tezepelumab (TZP). By blocking TSLP, TZP may produce wide-ranging effects. Based on positive clinical trial results, TZP appears to offer a promising, safe, and effective treatment approach. This narrative review examines the evidence for treating severe asthma with TZP, analyses clinical trial findings, and provides clinicians with practical insights into identifying patients who may respond best to this novel biologic therapy.